Grape skin fermentation by Lactobacillus fermentum CQPC04 has anti-oxidative effects on human embryonic kidney cells and apoptosis-promoting effects on human hepatoma cells. Issue 8 (29th January 2020) - Liu, Jia; Tan, Fang; Liu, Xinhong; Yi, Ruokun; Zhao, Xin
Abstract : Studies on the antioxidant effects of grapes have attracted increasing interest. Abstract : Studies on the antioxidant effects of grapes have attracted increasing interest. We used Lactobacillus fermentum CQPC04 to ferment grape skins. Components of the fermentation solution were separated and identified via high-performance liquid chromatography, and polyphenol compounds, including resveratrol and epicatechin, were isolated and identified from the fermentation solution. The major fermentation production components were assessed for their antioxidative abilities when administered under H2 O2 -induced oxidative damage in cell culture models. The fermentation solution significantly reduced oxidative damage, increased the expressions of the superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and GSH-peroxidase (GSH-Px) antioxidant genes and proteins in human embryonic kidney (293T) cells, stimulated the indices of total antioxidant capacity (T-AOC), SOD, CAT, GSH, and GSH-Px, and inhibited the indices of lactate dehydrogenase (LDH), malondialdehyde (MDA), and nitric oxide (NO), and the fermentation solution alleviated the increase in glutathione oxidized (GSSG) caused by oxidative damage, and the ratio of GSH/GSSG was up-regulated compared to the damage group. The fermentation solution also accelerated Human hepatoma (HepG2) cell death. Applying the fermentation solution to HepG2 cells significantly altered the cell morphology. HepG2 cell apoptosis and cell cycles were detected via flow cytometry. The fermentation solution promoted the apoptotic rate, and more cells were retained in the G2 phase, which prevented cells from further dividing. In the fermented group, the mRNA expression levels of Bcl-2, cox-2, PCNA, CD1, C-myc, CDK4, NF-κB and pRb1 were significantly decreased, and the expression levels of Caspase-3, Caspase-7, Caspase-8, Caspase-9, p53, TGF-β, and p21 were higher than those in the normal group. Phospho-NF-κB (p65), Bax and Caspase-8 protein expression increased, and NF-κB (p65) protein expression decreased. Protein expression levels also promoted apoptosis. Fermented grape skin solution is bioavailable in vitro and may help prevent oxidation and cancer cell proliferation.